The Fundamental Impact On Mining Share Price On Indonesia Stock Exchange (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research was conducted to determine the effect of the Debt to Equity Ratio, Return on Equity, Net Profit Margin  and Earning per Share to the share price of the subsector companieslisted coal mining. The sample is 41 companies registered in the coal mining sub-sector in 2017-2019. In this research The variables studied consisted of Debt to Equity Ratio, Return on Equity, Net Profit Margin  and Earning per Share as variables independent and share price as the dependent variable. Methods of analysis are used is multiple linear regression analysis. This research uses SPSS software. The results showed that partially variables DER, ROE, NPM and EPS, have an effect on stock prices. All variables simultaneously affect the stock price.